Contribution of Rahn Agreement Financing and Musyarakah Financing to Profitability in Sharia Commercial Banks in Indonesia for the 2021-2023 Period - Anwar, Khairil; Marjulin; Hilmi, (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to determine the contribution of Rahn Agreement Financing and Musyarakah Agreement Financing to Profitability in Sharia Commercial Banks. The research method used is quantitative research. The type of data used in this research is secondary data obtained from published financial reports at the OJK for each Sharia Commercial Bank for the 2021-2023 period. Data processing using the Eviews application, the results of the t test show that the financing contribution of the rahn contract has a significant effect on profitability, meaning that the independent variable rahn provides profits to BUS, meanwhile the results of the t test on the contribution of the musyarakah contract have a positive effect on profitability. Therefore, the independent variable musyarakah contributes profits to the BUS. The results of the next research using the F Test show that the variables Rahn Contract Financing and Musyarakah Contract Financing have a joint influence on the profitability of Sharia Commercial Banks. It can be concluded that the contribution of rahn contract financing and contract financing Musyarakah has a positive and significant effect on profitability at Sharia Commercial Banks. BUS must maintain consistency in the distribution of rahn and musyarakah contract financing so that profitability grows each period and continue to provide the latest innovations in rahn and musyarakah contract financing so that more and more people are interested in these two independent variables.